Preliminary and Comparative Experiment Study Between F-Flurpiridaz and N-NHHO Myocardial Perfusion Imaging With PET/CT in Miniature Pigs - Jiao Wang MD; Shuai Li Mpharm; Tian-wen Liu BS; Jie-min Zhang MD, PhD; Yue Chen MD; Jian-ming Li MD, PhD; Wen-gui Xu MD, PhD (Molecular Imaging)
Objectves: To comparatively explore the differences between 18 F-Flurpiridaz and 13 N-NH 3 ·H 2 O PET/CT myocardial perfusion imaging in miniature pigs. Methods: Ten Bama minipigs were divided into normal group and myocardial infarction group. The changes of the ratio of left ventricular myocardium to main organs with time were calculated and the best imaging time was confirmed for 18 F-Flurpiridaz imaging in normal group. The image quality score, summed rest score(SRS), Extend, total perfusion deficit(TPD) and left ventricle ejection fraction(LVEF) were respectively compared for 18 F-Flurpiridaz and 13 N-NH 3 ·H 2 O in infarction group. Results: 18 F-Flurpiridaz was rapid distributed in myocardium, and the background counts of cardiac cavity were very low, and no obvious interference extracardiac radioactivity was observed. The radioactive ratio of the left ventricular myocardium to cardiac blood pool and adjacent liver were high. Compared with 13 N-NH 3 ·H 2 O, there were no significant differences in functional parameters, including SRS, Extend, TPD and LVEF. Conclusion: The results preliminaryly show that 18 F-FIurpiridaz is a promising positron MPI agent with good image quality, ability of accurately evaluating cardiac function, and also convenience for application.